English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a)al+h2so4>al2(so4)3+h2

2006-12-01 01:53:27 · 3 answers · asked by Vince P 1 in Science & Mathematics Chemistry

3 answers

Al + H2SO4 -> Al2(SO4)3 + H2

There are 3 SO4s and 2 Als on the right, so
2Al + 3H2SO4 -> Al2(SO4)3 + H2

Then to balance the H,
2Al + 3H2SO4 -> Al2(SO4)3 + 3H2

Voila! You're done :)

2006-12-01 01:58:51 · answer #1 · answered by donteatflowers 2 · 0 0

Al + H2SO4-> Al2(SO4)3+H2
Left rIGHT
Al=1 Al=2
H=2 H=2 -
S=1 S=3
O=12 O=4

So,
Add a 2 on the left with A. So the eq is:
2Al + H2SO4-> Al2(SO4)3+H2
and,
Left rIGHT Al=2 Al=2 -
H=2 H=2 -
S=1 S=3
O=12 O=4
Now H is already solved. So move on to S.
Add 3 with h2so4. the eq becomes:
2Al + 3H2SO4-> Al2(SO4)3+H2
And,
Left Right
Al=2 Al=2 -
H=2 H=2 -
S=3 S=3 -
O=12 O=12-

Tha da.

2006-12-01 10:21:08 · answer #2 · answered by Ewnet 3 · 0 0

Al+H2SO4------>Al2(SO4)3+H2

(a) first: look at 2 in aluminum sulfate. So put a 2 in front of Al on the left. This balances the Al
(b) second: look at 3 in aluminum sulfate. So put a 3 in front of sulfuric acid. This balances the (SO4) sulfate ions
(c) You have now 6H on the left.....so put a 3 in front of hydrogen H2 on the right. This balances the Hydrogen atoms

2Al+3H2SO4------>Al2(SO4)3+3H2

2006-12-01 10:04:45 · answer #3 · answered by pete 2 · 0 0

fedest.com, questions and answers